Respuestas

  • Usuario de Brainly
2013-09-04T03:59:14+02:00
X = número
x + 1 = consecutivo

x . (x + 1) = 1260
x² + x - 1260 = 0
Aplicamos bascara
        –b ± √ b² – 4ac
x = ▬▬▬▬▬▬▬           siendo a = 1    b = 1    c = - 1260
              2a


      –1 ± √ 1 – 4(1)(-1260)
x = ▬▬▬▬▬▬▬
              2

      –1 ± √ 1 +  5040
x = ▬▬▬▬▬▬▬
              2

      –1 ± √ 5041
x = ▬▬▬▬▬▬▬
              2

      – 1 ± 71
x = ▬▬▬▬▬▬▬
              2

x1= (-1+71)/2 → x1= 70/2 → x1 = 35
x2 = (-1 -71) /2 → x2= - 72/2 → x2= - 36


Entonces los números son 35 y 36
 tambien pueden ser  - 36 y  - 35

espero que te sirva, salu2!!!!